Chemical and pharmaceutical manufacturing metrology support электронный курс - Пикула, Н. П. химик доцент Томского политехнического университета, кандидат химических наук 1949- (TPU Moodle, 2020)
The main goal of the course is to obtain theoretical and practical knowledge, skills and abilities in the field of metrological provision of chemical and pharmaceutical manufactures. The course is intended for 1st year students of the basic educational program for the preparation of masters "Analysis and control in chemical and pharmaceutical manufactures" direction of training 04.18.01 Chemical technology.